A new species of Diphascon (Tardigrada: Hypsibiidae) from Northern China supported by integrated taxonomy - Sun, Xue-Ling; Zhang, Jing-Yu; Wang, Ning; Zhao, Min; Luo, Xue-Gang (Zootaxa, 2020)
Morphological and molecular analyses have determined that there is a new species of Tardigrada found in China. Diphascon wuyingensis sp. nov., has smooth cuticle, pharyngeal apophyses, three rod-shaped macroplacoids (increasing in length from first to third, with the second macroplacoid clearly longer than the first) and lacks microplacoids and septulum. The new species has a very small drop-shaped formation and small claws of the Hypsibius type, but no pseudolunules or other cuticular thickenings. Three individual specimens and a group of four specimens were used for DNA isolation and 18S rRNA and COI sequencing; the p-distances to another three Diphascon species used for comparison varied in ranges of 8.8–10.2% (18S rRNA) and 24.2–26.7% (COI).